KOALISI PETANI MERICA DI DESA SAMBAHULE KECAMATAN BAITO KABUPATEN KONAWE SELATAN - Cici Hartiani; Syamsumarlin Syamsumarlin; Ashmarita Ashmarita (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
The purpose of this study is to find out and describe the horizontal coalition and vertical coalition built by pepper farmers in Sambahule Village, Baito District, South Konawe Regency. The informants in this study are 8 pepper farmers in the village of Sambahule. Data collection is done by using field research. Data collection of this study used the techniques of direct observation and in-depth interviews. Data analysis is qualitative descriptive. The results show that (1) Horizontal coalitions built by pepper farmers in Sambahule Village, namely cooperation between farmers and fellow farmers (2) Vertical coalitions built by pepper farmers in Sambahule Village, namely coalition with government, means traders production, collecting traders, and NGOs with farmers in Sambahule Village.